Fundamentals of communications and networking - Solomon, Michael [ (Michael G.)] , 1963-; Kim, David (Jones & Bartlett Learning, 2013)
Networks have long been regarded as methods to connect resources. While this is still the case, today's networks are required to support an increasing array of real-time communication methods. Video chat, real-time messaging, and always-connected resources put demands on networks that were previously unimagined. Fundamentals of Communication and Networking helps readers understand today's networks and the way they support the evolving requirement of different types of organizations. It covers the critical issues of designing a network that will meet an organization's performance needs and discusses how businesses use networks to solve business problems. Using examples and exercises, this book incorporates hands-on activities to prepare readers to proficiently understand and design modern networks and their requirements